(3NdGUI GdCbhGd aj eYQaI GdQLGds - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3CeG HYO , aEf GdYde HMGd GdQhGI ef CSGS GdCMcGe GdTQYjI aOYGfG Pdc Edi JUfja eNJUQ aj HjGf MGd GdQhGI s
(3BNQgG (B:s
(3hGdHGbi ef GdQhGjGJ Edi gDdGA GdeTGjN hEdi ZjQge ePchQ ai cJGHfG GdcHjQ, ef CQGOg hba Ydjg gfGc s
(3GfXQ GjVG HQbe (B230 (3JGQjNs
(3YdjgG oebGHdI SfI (B1103(3g`s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs